1996
DOI: 10.1001/archneur.1996.00550120105023
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Volume and Proximity to Onset in Presymptomatic Huntington Disease

Abstract: The results suggest that atrophy of the basal ganglia occurs gradually, beginning years before symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
3
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 7 publications
11
148
3
1
Order By: Relevance
“…Given the resilience of these findings, which have been demonstrated consistently across multiple studies in preHD,22, 23, 24, 25, 26, 27, 28, 29 we would suggest that analyses of subcortical volume becomes a minimum requirement for any future preclinical disease modifying trials in HD. Notably, structural volumetric analyses are likely to be more robust across scanners than resting‐state functional neuroimaging measures; therefore, they are also more likely to form a tractable basis for a standardized polymarker that can be used to integrate findings across studies and sites.…”
Section: Discussionmentioning
confidence: 73%
“…Given the resilience of these findings, which have been demonstrated consistently across multiple studies in preHD,22, 23, 24, 25, 26, 27, 28, 29 we would suggest that analyses of subcortical volume becomes a minimum requirement for any future preclinical disease modifying trials in HD. Notably, structural volumetric analyses are likely to be more robust across scanners than resting‐state functional neuroimaging measures; therefore, they are also more likely to form a tractable basis for a standardized polymarker that can be used to integrate findings across studies and sites.…”
Section: Discussionmentioning
confidence: 73%
“…Even though striatal atrophy has been detected and reported by many investigators (3,(25)(26)(27)(28)(29), neuronal degeneration also occurs in other areas of the brain such as the cerebral and cerebellar cortex (4,5), amygdala, hippocampus, and brainstem (6), supporting the concept that HD is a multisystem disorder. In agreement with this concept, subcortical gray matter loss in the thalamus, substantia nigra, and anterior basomedial diencephalic region has been described, but in later stages of the disease (5).…”
Section: Discussionmentioning
confidence: 92%
“…), was blinded to participant characteristics and completed all measurements for the study. Measurements were made by manually drawing boundaries of the caudate (head and body) and putamen, as previously described (Aylward et al, 1996;Aylward et al, 1997), and volumes were calculated based on the number of identified pixels. Caudate and putamen volumes were summed to obtain a measure of total striatal volume.…”
Section: Participant Characterizationmentioning
confidence: 99%
“…Several studies have documented structural and functional brain changes in CAG-expanded individuals who have not yet been diagnosed (Aylward et al, 1996;Aylward et al, 2000;Aylward et al, 2004;Kipps et al, 2005;Paulsen et al, 2006b;Reading et al, 2004). Although relatively few studies have investigated the association between cognition and brain changes in HD, a recent study showed that cognitive task performance correlated with cerebral white matter and striatal volumes in early HD (Beglinger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%